Which grab bar do you prefer in the bathroom?. Issue 4 (18th December 2017) - Morales, Ernesto; Pilon, Marc-Antoine; Doyle, Olivier; Gauthier, Véronique; Gamache, Stéphanie; Routhier, François; Rousseau, Jacqueline
Abstract : Purpose: The purpose of this paper is to verify whether the horizontal grab bar for the toilet and the bathtub suggested by the Code du bâtiment du Québec conform to users' preferences. Perceived effort, comfort and safety were considered. Design/methodology/approach: In total, 31 adults and seniors using manual and powered wheelchairs were asked to test different grab bar configurations for both the toilet and bathtub. A questionnaire was designed to evaluate participants' perceptions and preferences after the trials with each grab bar. Effort was measured using the ten-level Borg scale, while participants' comfort and safety were assessed with a five-point Likert scale. Participants were finally invited to express an overall personal preference between the two grab bar used in each setup. Findings: Participants showed preference for an L-shaped grab bar for the toilet, and a horizontal grab bar for the bathtub. The authors' results differ from the recommendations of the barrier-free design standards of the province of Quebec's construction code, which states that horizontal grab bars should be used for the toilet and bathtub. Originality/value: This study suggest that despite the limited sample, there is an undeniable need for testing norms for public spaces, whenever is possible and has a direct effect on end-users, before publishing them.